Land use development and environmental responses since the Neolithic around Lake Paladru in the French Pre-alps. (June 2016) - Doyen, E.; Bégeot, C.; Simonneau, A.; Millet, L.; Chapron, E.; Arnaud, F.; Vannière, B.
Abstract: The Lake Paladru sedimentary archive documents the past 10, 000 years of the environmental history of the French Pre-alps. The archive's information on vegetation dynamics, fire activity and soil erosion serves to reconstruct a continuous dynamic record of land use over the last 6000 years. This multi-proxy approach serves to document the effects of successive human settlements on the environment at the watershed scale. First, discrete human impacts were identified during the Middle Neolithic that have not yet been confirmed by archaeological discoveries in the watershed. Developments of agropastoral activity have been recorded during the Late Neolithic (the period of the pile-dwelling archaeological site "Les Baigneurs") and the Bronze Age, and the practice of slash-and-burn is documented by the records of fires. During the Iron Age and the Roman period, agropastoral activities (livestock farming and cereal cultivation) became continuous. They involved an intensification of human effects with a rapid and high-amplitude increase in soil erosion and a shift in the use of fire from an instrument for clearing land to an agropastoral landscape management tool. The Medieval period was characterized by the spatial expansion and diversification of crops. Results of this study have located the "thousand-year" pile dwelling sites such as "Colletière" in a longer phase of human occupation that deeply and sustainably modified the surrounding landscape of the lake. Beginning in the Modern period, the proxies used in this study served to record a new shift in land use marked by extensive clearing and the abandonment of most crop areas. This shift was linked to the expansion of industrial activities and subsequently to their abandonment during the 20th century. Highlights: 6000 years of land-use reconstruction in the western Alps. Confrontation of palaeoecological and archaeological approaches to improve timing and extent of local human impact. Iron Age and Roman period as key periods of landscape modification. The combined study of micro- and macro-charcoals established changes in past use of fires.